Deverbal and denominal -(a)tan nouns in Old Sicilian - Luisa Brucale (Études romanes de Brno)
In this paper, I attempt to provide an initial description of the behaviour of nouns ending in -(a)ta in Old Sicilian, as evidenced by the texts collected in ARTESIA (14th-16th century). Deverbal and denominal nouns in -(a)ta are analysed in the context of theoretical insights provided by the reference literature on Italian and Romance languages. Based on this, it is possible to confirm for Sicilian some of the characteristics previously identified for Italian nouns ending in -(a)ta. The analysis also helps to characterise the semantic core of the derivational process that creates these nouns, which serves to extract a discrete and identified entity from a general process or from a mass entity.